Justice in the Governance of Nations and Cultures through the Story of Dhul-Qarnayn A Comparative Analytical Study from an Islamic Philosophy Perspective: العدل في إدارة الشعوب والثقافات من خلال قصة ذي القرنين: دراسة تحليلية مقارنة من منظور فلسفي إسلامي - Majyd Kasheem; Abdulnasir Alsayd; Yousuf Aboujanah; Naima Salem Alzletni (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2025)
Justice is a supreme human value that most people agree is essential for the establishment and stability of societies and civilizations. The story of Dhul-Qarnayn, as mentioned in the Holy Quran in Surah Al-Kahf, serves as a vivid example of justice in managing society across social, political, and military dimensions through the actions of a faithful servant whom God empowered on earth. The story embodies various aspects of justice, from dealing with culturally and linguistically diverse nations to balancing material power with moral values. From an Islamic perspective, the story highlights the concept of a just leader who uses strength to support the oppressed and ensure security for communities through fair reward and punishment. Philosophically, the story offers insight into the relationship between ruler and ruled, and the interplay between good and evil as elements of justice. This research analyzes the concept of justice in the story of Dhul-Qarnayn from both Islamic and philosophical perspectives, focusing on points of comparison between them. It adopts an analytical approach to examine and interpret the text in light of divine justice, alongside a comparative method to explore similarities and differences between Islamic and philosophical views as presented in the Quranic narrative. The research concludes that Dhul-Qarnayn represents a unique model of divine justice. His actions reflect divine guidance, making the story a significant reference for justice in governance. Both perspectives share key principles, though they differ in their foundational frameworks.